Breaking down barriers : youth with physical challenges - Esherick, Joan. (Broomall, Pa. : Mason Crest Publishers, 2004)
Discusses several different types of disabilities, their causes, and treatments.
A new neighbor : meeting someone with physical disabilities -- Cerebral palsy : surprised by Jen -- Not all disabilities are alike -- Amputation : an interview with Tyrone -- Traumatic spinal cord injury : an interview with Allison -- Spina bifida : an interview with Katie -- Muscular dystrophy : an interview with Ben -- Disabled, not unable.
Includes bibliographical references (p. 120) and index.
Keywords: Youth with disabilities -- Juvenile literature; People with disabilities; People with disabilities -- Juvenile literature